An ingeniously assembled metal–organic framework on the surface of FeMn co-doped Ni(OH)2 as a high-efficiency electrocatalyst for the oxygen evolution reaction. Issue 34 (5th August 2021) - Ye, Lei; Zhang, Yeqing; Zhang, Meilin; Gong, Yaqiong
Abstract : FeMn co-doped Ni(OH)2 nanosheets were grown in situ on the surface of nickel foam and then transformed into a MOF by etching strategy, which shows excellent OER performance and durability under alkaline conditions. Abstract : To overcome the problem of the sluggish kinetics of the oxygen evolution reaction (OER), it is of great significance to develop an efficient and stable non-noble metal-based OER catalyst for electrocatalytic energy conversion and storage. Herein, a complex of a metal–organic framework and hydroxide is synthesized by performing a ligand etching strategy on FeMn co-doped Ni(OH)2 nanosheets in situ grown on nickel foam (FeMn-Ni(OH)2 @MOF/NF). Benefiting from the unique sheet-on-sheet hierarchical structure, multi-metal active nodes and two active materials grown in situ, the resulting FeMn-Ni(OH)2 @MOF/NF demonstrated brilliant OER activity with an overpotential of 199 mV to achieve a current density of 10 mA cm −2 and long-term stability. This research will provide a new strategy for the design of high-performance OER electrocatalysts.